KUALITAS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (e-KTP) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN ENDE - Age, Karolus; Tanusi, Gabriel (ANALISIS, 2022)
Excellent service provided by service officers in the field of population registration, especially e-KTP loading, greatly affects the quality of service perceived by the community. Making e-KTP which take 2-4 weeks, lack of friendliness of employees is providing services, service provided are too bureaucratic, the numbers of officers who handle the e-KTP recording process is not comparable to the people who take care of making e-KTP are problems faced in managing the e-KTP. This study aims to determine the value of the community satisfaction index in getting public services at the office of population and civil registration in ende regency, especialy the process of making e-KTP. The population in this study amounted to 9.811 people with a total sampel of 99 people. Date collection techniques using questionnaires, interviews and documentation. The dat a of analysis technique uses an analysis of the community satisfaction index which is calculated using the weighted average value of each service element. The result of the study show that the community satisfaction index in obtaining e-KTP making services at the ende regency popilation and civil registration office uses 12 elements or assessment indicators coverted to 37,50 and is in the category of poor service quality, while the average value of the community satisfaction indeks studied based on the characteristics of the respondents is 1,39 and is the category of poor service quality